Changes in Nursing Students' Career Choices Following the COVID-19 Pandemic in China - Bai, Wei; Xi, Hai-Tao; Zhu, Qianqian; Wang, Zhiwen; Han, Lin; Chen, Pan; Cai, Hong; Zhao, Yan-Jie; Chen, Li; Ge, Zong-Mei; Ji, Mengmeng; Zhang, Hongyan; et al. (Frontiers in Psychiatry, 2021)
Abstract Background: Health professionals including nurses have experienced heavy workload and great physical and mental health challenges during the coronavirus disease 19 (COVID-19) pandemic, which may affect nursing students’ career choices. This study examined the changes in nursing students’ career choices after the COVID-19 pandemic in China. Methods: This study was conducted in five university nursing schools in China between September 14, 2020 and October 7, 2020. Career choices before and after the COVID-19 pandemic were collected and analyzed. Results: In total, 1,070 nursing students participated in the study. The reported choice of nursing as future career increased from 50.9% (95% confidence interval (CI): 47.9% - 53.9%) before the COVID-19 pandemic to 62.7% (95%CI: 59.8% - 65.6%) after the onset of COVID-19 pandemic. Students who chose nursing as their future career following the COVID-19 outbreak had less severe depression and anxiety compared to those who did not choose nursing, but the associations of depression and anxiety with career choice disappeared in multivariable analyses. Binary logistic regression analysis revealed that male gender (odds ratio (OR)=0.68, 95% CI: 0.50-0.91), rural residence (OR=1.53, 95%CI: 1.17-2.00), fourth year students (OR=0.50, 95%CI: 0.35-0.72), negative experiences during the COVID-19 pandemic (OR=0.66, 95%CI: 0.47-0.92), and good health (OR=4.6, 95%CI: 1.78-11.87) were significantly associated with the choice of nursing as future career after the onset of the COVID-19 pandemic. Conclusions: The COVID-19 pandemic appeared to have a positive influence on the career choice of nursing among Chinese nursing students.